2015
DOI: 10.1097/scs.0000000000001399
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Morbidity and Mortality in Patients Undergoing Skull Base Reconstruction

Abstract: The relative rarity of skull base tumors has limited surgeons' ability to report on morbidity and mortality in a large and nationwide patient series. We aimed to assess the impact of reconstructive procedures on patients undergoing skull base surgery and to determine whether 30-day postoperative morbidity and mortality varied between patients who underwent reconstruction and those who did not. We performed a retrospective analysis using American College of Surgeons National Surgical Quality Improvement Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Many authors have reported postoperative complications of skull-base surgery and its risk factors. 1,[4][5][6][7] The reported complication rate is 11.5 to 63%, 1,4,5 reflecting a certain width of range. One of the largest series among them, which included 1,193 cases, 1 showed a complication rate of 36.3% and described medical comorbidity, history of radiation therapy, and the extent of intracranial tumor involvement as independent predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have reported postoperative complications of skull-base surgery and its risk factors. 1,[4][5][6][7] The reported complication rate is 11.5 to 63%, 1,4,5 reflecting a certain width of range. One of the largest series among them, which included 1,193 cases, 1 showed a complication rate of 36.3% and described medical comorbidity, history of radiation therapy, and the extent of intracranial tumor involvement as independent predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have developed systems for the classification of skull-base defects. [5][6][7][8][9] Urken et al presented a classification system for skull-base reconstruction based on the resected regions other than the skull-base. 5 The classification system was a little complicated and complications were not compared based on the classification in his study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the current study aimed to focus on the morbidity and mortality profile of only the ablative/resection component of open anterior skull base surgery, and did not factor in reconstruction. In light of this, an ACS‐NSQIP study comparing those cases that underwent skull base reconstruction and those that did not found that there was no significant difference in complications, death, or length of stay between the two groups . Fourth, it is worthwhile to note that patients who undergo open approaches to the skull base tend to have significantly more advanced disease (e.g., skin, orbital, vascular involvement), indicating that patient selection is potentially biased toward worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Free flaps are versatile for reconstructing defects resulting from resections of the skull base, but the impact of reconstructive procedures on the overall morbidity and mortality of patients undergoing skull base surgery needs to be considered. Kim et al 17 analyzed the data of 199/479 patients who underwent reconstruction after skull base surgery. This study showed that additional measures involved in flap reconstruction are associated with an increasing operation time and return to the operating room rate but not with complications, morbidity, or mortality.…”
Section: Discussionmentioning
confidence: 99%